Burnout in hostels: How it shapes workers’ perceptions of human resources practices - Santos, M. E.; Dias, Á.; Patuleia, M. (Problems and Perspectives in Management, 2022)
There are scarce results on burnout in such organizations as hostels and how it influences workers’ perceptions of their companies. Therefore, this study aims to analyze burnout of hostel workers and assess how it influences their perceptions of the type of leadership, the kind of support, the existence of feedback sessions, the organizational climate, and the quality of T&D programs. Data were collected from 96 employees of Portuguese hostels; existing validated measures were adapted from relevant literature. A pilot test was conducted to ensure the accuracy of the measures according to the target population. A PLS analysis of survey data provided the following results. Burnout plays a negative role in employees' overall acknowledgment of the organization and their sense of satisfaction and loyalty toward it. Specifically, the most substantial negative effects of burnout were on feedback quality, manager support, and organizational climate (? = –0.557; –0.549; –0.542, p < 0.001, respectively). Furthermore, the indirect and negative effect of burnout on employee loyalty and employee satisfaction was also verified (? = –0.415; –0.418, p < 0.001, respectively). Therefore, managers can elaborate well-designed and applied practices based on these factors. Finally, this paper also discusses future research recommendations.